PROFILE OF MATHEMATICAL CRITICAL THINKING SKILLS OF VOCATIONAL HIGH SCHOOL STUDENTS BASED ON FACIONE INDICATORS IN STATISTICS - Dwi Anggraini; Revalina Ayu Natalia Hutabarat; Santa De Luisa Sitorus; Wildani Nisrina Nabilah; Budi Halomoan Siregar (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Mathematical critical thinking skills have become an essential competency in 21st-century learning, particularly in statistics, which requires in-depth analysis and reasoning. However, various findings indicate that students’ critical thinking skills have not yet developed optimally and still show imbalances across different aspects of thinking. This study aims to describe the profile of eleventh-grade students’ mathematical critical thinking skills at SMK Negeri 4 Medan based on critical thinking indicators. The study employed a qualitative approach with a descriptive method. The participants consisted of 14 students selected through purposive sampling in accordance with the context of statistics learning. Data were collected using an essay-based test and analyzed through descriptive techniques to illustrate students’ achievement across each indicator. The results show that students’ mathematical critical thinking skills are at a moderate level, with an average achievement of 57.1%. Students tend to perform better in understanding and analyzing problems, while their abilities in evaluating, drawing conclusions, and explaining reasoning remain relatively low. These findings indicate that students’ critical thinking skills have not yet developed comprehensively across all stages of thinking. Therefore, learning should be designed to systematically promote reasoning, reflection, and mathematical communication to support a more balanced and sustainable development of critical thinking skills. ABSTRAK Kemampuan berpikir kritis matematis menjadi kompetensi esensial dalam pembelajaran abad ke-21, terutama pada materi statistika yang menuntut analisis dan penalaran yang mendalam. Namun, berbagai temuan menunjukkan bahwa kemampuan tersebut pada siswa belum berkembang secara optimal dan masih menunjukkan ketidakseimbangan antar aspek berpikir. Penelitian ini bertujuan untuk mendeskripsikan profil kemampuan berpikir kritis matematis siswa kelas XI di SMK Negeri 4 Medan berdasarkan indikator berpikir kritis. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian berjumlah 14 siswa yang dipilih secara purposif sesuai dengan konteks pembelajaran statistika. Data dikumpulkan melalui tes esai dan dianalisis menggunakan teknik deskriptif untuk menggambarkan capaian kemampuan siswa pada setiap indikator. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis matematis siswa berada pada kategori sedang dengan rata-rata capaian sebesar 57,1%. Kemampuan siswa cenderung lebih baik pada tahap memahami dan menganalisis masalah, sedangkan pada tahap mengevaluasi, menarik kesimpulan, dan menjelaskan alasan masih tergolong rendah. Temuan ini menunjukkan bahwa kemampuan berpikir kritis siswa belum berkembang secara menyeluruh pada seluruh tahapan berpikir. Oleh karena itu, diperlukan pembelajaran yang secara terarah mendorong aktivitas penalaran, refleksi, dan komunikasi matematis agar pengembangan kemampuan berpikir kritis dapat berlangsung secara lebih seimbang dan berkelanjutan.